ICE BERGS AND PACK ICE IN THE ANTARCTIC OCEAN - Takeharu KUMAGORI; Saburo YANAGAWA; Tsutomu ISOUCHI; Isamu KOTAKE; Kanau MATSUIKE (National Institute of Polar Research, 1963)
During the cruise in the Antarctic Ocean on board the UMITAKA-MARU, Tokyo University of Fisheries, ice bergs and pack ice were observed from Dec. 3, 1961 to Jan. 30, 1962. About 2,000 bergs in total were counted within the water 10 miles from the ship. Many ice bergs concentrated especially in the water extending from Lat. 57°S to Lat. 61°S were supposed to have occurred closely related to the Antarctic Ocean current. Further, the north limit area of pack ice and bergs were observed during the survey.